Correlation pain-quality of life in women after being submitted to surgical treatment of breast cancer - dos Santos Mendes, Izabela; Takeshi Tatsukawa de Freitas, Sergio; de Castro Souza, Glaucia; Cesar Ribeiro dos Reis, Mariana; Queiroz de Souza, Djenifer; Pupio Silva Lima, Fernanda; Oliveira Andrade, Adriano; Oliveira Lima, Mario (O Mundo da Saúde, 2014)
Breast cancer, which is more prevalent in the female population, causes physical, functional, and emotional changes that make daily activities difficult, affecting women’s quality of life. The aim of this study was to characterize the influence of post mastectomy pain syndrome, correlating pain and quality of life. We conducted a descriptive exploratory study with a quantitative approach using the Quality of Life Questionnaire SF-36. The sample consisted of 49 women with a mean age of 53.9 ± 8.8 years, treated in Specialized Oncology Centers in the region. There was no significant difference between the pain domains compared to other domains. There was a high correlation between time after surgery, 3-6 years, and pain domain (r = 90). Older women had a significant increase in pain compared to younger ones (p = 05). This research found that the pain related to breast cancer is a debilitating clinical symptom, but not the primary factor for deficits in quality of life, which is mainly influenced by emotional aspects.